PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN TOKO BUKU TOGAMAS MALANG - Joko Samboro; Lina Budiarti; Eko Boedhi Santoso (Adbis: Jurnal Administrasi dan Bisnis, 2019)
The main objectives of this study are: a. To find out and analyze the significant influence between store atmosphere on Purchasing Decisions. B. To find out and analyze the significant influence between store atmosphere on Customer Loyalty through Purchasing Decisions. The research location is in the city of Malang, while the study population is all customers who have studied in the TogaMas store in the last three months, while the sample is one hundred. The results showed that the data used were valid and reliable, the better the Store Atmosphere and Purchasing Decisions, the stronger the Customer Loyalty with the influence of the total variables studied was 31.11%. This finding is expected to be beneficial for: a). For the Company, as input for decision making in determining business policies, especially related to marketing, especially as an evaluation material for the company. b). For Malang State Polytechnic, as input for improving the educational curriculum, especially in marketing management courses. c). For Advanced Researchers, a foothold can be used towards perfecting future research.